2018
DOI: 10.1111/echo.13846
|View full text |Cite
|
Sign up to set email alerts
|

Global longitudinal strain and long‐term outcomes in asymptomatic extracardiac sarcoid patients with no apparent cardiovascular disease

Abstract: In conclusion, among patients with extracardiac sarcoidosis and no symptoms of cardiovascular disease, even when EF is preserved, GLS seems to be strongly associated with adverse future events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 19 publications
1
25
0
Order By: Relevance
“…Nine studies reported LVGLS in our cohorts. 10,[15][16][17][18][19][20][21][22] The pooled mean LVGLS was significantly lower in the sarcoid group as compared with controls: standard mean difference (SMD) −3.98, 95%…”
Section: Re Sultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nine studies reported LVGLS in our cohorts. 10,[15][16][17][18][19][20][21][22] The pooled mean LVGLS was significantly lower in the sarcoid group as compared with controls: standard mean difference (SMD) −3.98, 95%…”
Section: Re Sultsmentioning
confidence: 99%
“…Of these, 28 full texts were screened and 9 studies were included in the final analysis with an aggregate of 967 patients: 589 in the sarcoid group and 378 in the control group. 10,[15][16][17][18][19][20][21][22] patients with cardiovascular symptoms. 23 The study flow chart is presented in Figure 1.…”
Section: Re Sultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Global longitudinal strain has been shown to be reduced in patients with extra-cardiac sarcoidosis but without overt evidence of cardiac involvement, indicating pre-clinical cardiac involvement prior to any reduction in LVEF or other ECG/echocardiographic abnormalities [46,47] (Figure 5). Moreover, this reduction in GLS has also been associated with poorer outcomes, including all-cause mortality, heart failure hospitalisation and malignant ventricular arrhythmias [46][47][48][49]. Furthermore, GLS is able to differentiate between patients with extra-cardiac (À19.6 AE 1.9%) and cardiac sarcoid (À14.7 AE 2.4%) with virtually no overlap between the two groups [50].…”
Section: Advanced Echocardiographic Imagingmentioning
confidence: 99%
“…Potential novel approaches to monitoring cardiac sarcoidosis include global longitudinal strain detected by echocardiography [7], serum biomarkers of cardiac injury [8][9][10][11], and miniaturized insertable cardiac monitors. However, currently there are inadequate data to recommend any of these approaches for monitoring cardiac sarcoidosis.…”
mentioning
confidence: 99%